2015
DOI: 10.2147/dddt.s78277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective effects of curcuminoid (curcumin and bisdemethoxycurcumin)-loaded liposomes against bone turnover in a cell-based model of osteoarthritis

Abstract: Curcumin (Cur) and bisdemethoxycurcumin (BDMC), extracted from Curcuma longa, are poorly water-soluble polyphenol compounds that have shown anti-inflammatory potential for the treatment of osteoarthritis. To increase cellular uptake of Cur and BDMC in bone tissue, soybean phosphatidylcholines were used for liposome formulation. In this study, curcuminoid (Cur and BDMC)-loaded liposomes were characterized in terms of particle size, encapsulation efficiency, liposome stability, and cellular uptake. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 51 publications
4
35
0
Order By: Relevance
“…This process is a result of osteoclast activation known as osteoclastogenesis [19]. The receptor activator NF-kappa ligand (RANKL) is produced by some cells as the osteoblast and has an affinity for RANK, which is present in the membrane of osteoclast precursor cells [20].…”
Section: Physiopathology and Cartilage Destructionmentioning
confidence: 99%
See 3 more Smart Citations
“…This process is a result of osteoclast activation known as osteoclastogenesis [19]. The receptor activator NF-kappa ligand (RANKL) is produced by some cells as the osteoblast and has an affinity for RANK, which is present in the membrane of osteoclast precursor cells [20].…”
Section: Physiopathology and Cartilage Destructionmentioning
confidence: 99%
“…Moreover, curcumin has been shown to inhibit the activator protein 1 (AP-1) pathway and NF-κB leading to the suppression of the production of MMP-3, MMP-9, and MMP-13 [15,19]. Zhang et al [9] demonstrated in a mouse model that the production of MMP-1, MMP-3, MMP-13, IL-1β,TNF-α, and ADAMTS5 was decreased when the animals were treated with curcumin.…”
Section: The Potential Effects Of Curcuma Longamentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to prevent the destructive changes in joints and periarticular bone seems to be comparable to that of betamethasone [38,39]. Liposomal encapsulation may help overcome the poor bioavailability problem generated by the low water-solubility [40]. The osteoclast-osteoblast balance is tipped in favor of bone building, while halting the OA progression [40].…”
Section: Curcuma Spp Fam Zingiberaceaementioning
confidence: 99%